Interaction Between Dakwah and Local Culture - M. Sabir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the interaction between da'wah and local culture as a dynamic process that influences the effectiveness of conveying Islamic teachings within society. Da'wah does not occur in a vacuum, but rather confronts values, traditions, and cultural characteristics that are deeply rooted in social life. Therefore, understanding local culture is key to formulating adaptive, persuasive, and humanistic da'wah strategies. The study's findings indicate that harmonizing Islamic values ​​and local wisdom can foster broader acceptance, strengthen religious identity, and preserve community culture. However, challenges arise when local culture contains elements that conflict with Islamic principles, necessitating a wise and contextual da'wah approach. Overall, the interaction between da'wah and local culture plays a crucial role in shaping a da'wah approach that is more effective, inclusive, and relevant to the social and cultural developments of the community.